SCHOOL COMMITTEE PERFORMANCE IMPROVEMENT MANAGEMENT MODEL IN SUCCESSFULLY IMPLEMENTING THE INDEPENDENT CURRICULUM IN PRIVATE SCHOOLS IN BATAM CITY - Tumpal Manurung; Dahrul Aman Harahap; Ramdhani (RADJA PUBLIKA, 2025)
The school committee is an independent institution consisting of parents/guardians of students, school communities, community leaders, education experts who care about education. This study is targeted to identify and analyze the planning, implementation, and evaluation strategies for the progressiveness of the School Committee's performance as a manifestation and implementation of the independent curriculum. The techniques and methods used in completing this study focus on a qualitative perspective through observation, interviews, and documentation and are targeted to identify linear research findings on the planning, implementation, and evaluation strategies for the progressiveness of the School Committee's performance as a manifestation and implementation of the independent curriculum. Based on the target findings, the research focuses on three stages of management, namely planning, implementation and evaluation and analysis of the school committee's performance progressiveness strategy as a manifestation and implementation of the independent curriculum. The research findings are expected to have a management model implemented in the independent curriculum obtained from the collaboration of the School Committee's performance for four years which is constrained by a number of main challenges, namely the school committee's agenda for the success of short-term, medium-term and long-term targets in the school year that has been set.